2015
DOI: 10.1111/tbed.12356
|View full text |Cite
|
Sign up to set email alerts
|

Three Different Routes of Inoculation for Experimental Infection with Schmallenberg Virus in Sheep

Abstract: Schmallenberg virus (SBV) is an emerging Orthobunyavirus affecting European domestic ruminants. In this study, three groups of ewes (n = 3) were inoculated with 1 ml of an SBV infectious serum, via the subcutaneous (SC), intradermal (ID) or intranasal (IN) route. The ewes were monitored for 10 days and no clinical signs were reported. IN inoculation failed to generate any detectable RNAemia. SC and ID inoculation induced typical SBV RNAemia and seroconversion upon day 6 post-inoculation in 3/3 and 2/3 sheep, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…To the best of our knowledge, this is the first time SBV RNA has been detected in these species. The low frequency of SBV RNA-positive animals is consistent with the short duration of viraemia detected in domestic ruminants [ 22 ,43, 41 ]. The presence of SBV RNA-positive animals confirms the circulation of the virus during the years 2011 and 2015.…”
Section: Discussionsupporting
confidence: 60%
“…To the best of our knowledge, this is the first time SBV RNA has been detected in these species. The low frequency of SBV RNA-positive animals is consistent with the short duration of viraemia detected in domestic ruminants [ 22 ,43, 41 ]. The presence of SBV RNA-positive animals confirms the circulation of the virus during the years 2011 and 2015.…”
Section: Discussionsupporting
confidence: 60%
“…As meconium is an end-product of the amniotic fluid being swallowed by the fetus during gestation time, it is likely that SBV detection in the meconium could reflect the former transient presence of the virus in the amniotic fluid. Fecal shedding was reported following SBV experimental infection in heifers [ 46 ] and ewes [ 47 ]. Hence positive SBV RNA detection in meconium might be the in utero version of the previously reported positive detection in the feces of adult animals.…”
Section: Discussionmentioning
confidence: 99%
“…In several recent studies [14] clinical signs reported in BTV infected animals were of a lesser extent than those reported from the field [14,17,27,28,32,33,34]. As modified live vaccines gain their attenuation through serial cell passages, the first and most obvious hypothesis to explain the mild severity of bluetongue disease in the experiment is the use of culture grown virus.…”
Section: Studying the Pathogenesis And Immune Response Of Btv And mentioning
confidence: 99%
“…Several authors including us [17] used mixed routes to overcome the respective disadvantages of each approach (Table 1; [34,54]). In a study of our group, we compared intranasal, intradermal and subcutaneous routes for experimental infections of ewes with SBV [28]. Intradermal is an interesting yet underused route: indeed most haematophagous arthropods do not pass the skin and their mouthparts only allow them to feed intradermally.…”
Section: Studying the Pathogenesis And Immune Response Of Btv And mentioning
confidence: 99%
See 1 more Smart Citation